The Benefit of DLBS3233 as Add-on Therapy for Symptomatic Painful Diabetic Neuropathy: Case Series - Rizaldy Taslim Pinzon; Abraham Al Jody; Nicholas Adriel Pinzon (PT Dexa Medica, 2025)
Symmetrical painful diabetic neuropathy (PDN) is a highly prevalent form of diabetic peripheral neuropathy with significant morbidity. Despite its high prevalence, the optimal treatment of this condition remains a clinical challenge. There was an emergence need for add-on therapy that more focused on the dimensions of inflammation and toxic oxidative stress.Previous evidences from placebo-controlled studies have shown that opioids, antiepileptic, and antidepressant drugs are effective for alleviating PDN symptoms. In many cases, safety issues regarding potential side effects of those drugs limit the optimal use of the medications. We report case series of painful diabetic neuropathy in type 2 diabetic patients. DLBS3233 was given as add-on therapy to standard oral antidiabetic medication or insulin and adjuvant analgesics for all patients. After 3 months follow up, there was modest pain reduction and improvement in blood glucose control in allpatients. DLBS3233 was well tolerated in all patients.